Improving the Therapeutic Effect of Ultrasound Combined With Microbubbles on Muscular Tumor Xenografts With Appropriate Acoustic Pressure - He, Yan; Yu, Meiling; Wang, Jie; Xi, Fen; Zhong, Jiali; Yang, Yuwen; Jin, Hai; Liu, Jianhua (Frontiers in Pharmacology, 2020)
Ultrasound combined with microbubbles (USMB) is a promising antitumor therapy because of its capability to selectively disrupt tumor perfusion. However, the antitumor effects of repeated USMB treatments have yet to be clarified. In this study, we established a VX2 muscular tumor xenograft model in rabbits, and performed USMB treatments at five different peak negative acoustic pressure levels (1.0, 2.0, 3.0, 4.0, or 5.0 MPa) to determine the appropriate acoustic pressure. To investigate whether repeated USMB treatments could improve the antitumor effects, a group of tumor-bearing rabbits was subjected to one USMB treatment per day for three consecutive days for comparison with the single-treatment group. Contrast-enhanced ultrasonic imaging and histological analyses showed that at an acoustic pressure of 4.0 MPa, USMB treatment contributed to substantial cessation of tumor perfusion, resulting in severe damage to the tumor cells and microvessels without causing significant effects on the normal tissue. Further, the percentages of damaged area and apoptotic cells in the tumor were significantly higher, and the tumor growth inhibition effect was more obvious in the multiple-treatment group than in the single USMB treatment group. These findings indicate that with an appropriate acoustic pressure, the USMB treatment can selectively destroy tumor vessels in muscular tumor xenograft models. Moreover, the repeated treatments strategy can significantly improve the antitumor effect. Therefore, our results provide a foundation for the clinical application of USMB to treat solid tumors using a novel therapeutic strategy.